2012
DOI: 10.2134/jeq2011.0284
|View full text |Cite
|
Sign up to set email alerts
|

Precision Placement of Separated Dairy Sludge Improves Early Phosphorus Nutrition and Growth in Corn (Zea mays L.)

Abstract: Efficient use of manure nutrients by crops is necessary to minimize losses to the environment. This field study examined the possibility of replacing side-banded mineral P with precision-placed high-P sludge (6.2-11.0% dry matter) obtained after settling dairy manure slurry. The sludge was injected at about 30 kg P ha (36.0-51.2 m ha) into the soil at corn row spacing, and the corn was planted 5, 10, and 15 cm beside the injection furrow. Controls included no added P and side-banded commercial P fertilizer. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…These results also suggest that long‐term WS and LF applications would not impede early uptake of P or other nutrients by limiting AMF colonization in corn. The insensitivity of AMF colonization to P treatments is consistent with Kabir et al (1997) and Bittman et al (2006, 2012) but in contrast with Grant et al (2005).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…These results also suggest that long‐term WS and LF applications would not impede early uptake of P or other nutrients by limiting AMF colonization in corn. The insensitivity of AMF colonization to P treatments is consistent with Kabir et al (1997) and Bittman et al (2006, 2012) but in contrast with Grant et al (2005).…”
Section: Resultssupporting
confidence: 88%
“…In 2016, amending the control with starter P (P+) increased shoot P uptake to approximately the levels of the high WS plots with no starter (P−), but starter P increased shoot biomass and P uptake of high WS plots by >50% (34% in 2015), despite >1000 kg ha −1 net P surplus over 11 yr in these plots. These results help to explain the common farm practice of supplying corn with starter commercial fertilizer, even on soils with histories of high manure P application rates and soil‐test P (Bittman et al, 2012; Schröder et al, 2015). Overall, legacy P did not obviate the need of starter for juvenile corn.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…This has previously been observed with mineral fertilizers (Rasmussen et al, 1996;Blackshaw, 2005) and animal slurry on corn (Schröder et al, 1997;Rasmussen, 2002;Petersen, 2005;Bittman et al, 2012). In the case of animal slurry, placement close to the seed row has been shown to increase yield in spring cereals (Petersen, 2005) and phosphorus (P) uptake in corn (Schröder et al, 1997;Bittman et al, 2012). Rasmussen et al (1996) observed 55% less weed biomass and 28% higher yield of spring barley after application of fertilizer close to the crop row compared with broadcasting.…”
Section: Introductionmentioning
confidence: 61%
“…This justifies pellet placement close to the row, instead of broadcasting or placement mid-way between rows, as this can increase nutrient availability for the crop and reduce it for weeds (Rasmussen et al, 1996). This has previously been observed with mineral fertilizers (Rasmussen et al, 1996;Blackshaw, 2005) and animal slurry on corn (Schröder et al, 1997;Rasmussen, 2002;Petersen, 2005;Bittman et al, 2012). In the case of animal slurry, placement close to the seed row has been shown to increase yield in spring cereals (Petersen, 2005) and phosphorus (P) uptake in corn (Schröder et al, 1997;Bittman et al, 2012).…”
Section: Introductionmentioning
confidence: 88%